Chicken Little - Emberley, Rebecca; Emberley, Ed. (New York : Roaring Brook Press, 2009)
An illustrated retelling of the story in which Chicken Little becomes convinced the sky is falling after being hit on the head by an acorn.
"A Neal Porter Book.".
Kirkus Starred.
2.8
K-3
Keywords: Chickens -- Folklore; Chickens -- Folklore; Folklore; Chickens -- Folklore; Folklore